DSCAM localization and function at the mouse cone synapse. Issue 11 (2nd June 2014) - de Andrade, Gabriel Belem; Long, Samuel S.; Fleming, Harrison; Li, Wei; Fuerst, Peter G.
ABSTRACT The Down syndrome cell adhesion molecule (DSCAM) is required for regulation of cell number, soma spacing, and cell type–specific dendrite avoidance in many types of retinal ganglion and amacrine cells. In this study we assay the organization of cells making up the outer plexiform layer of the retina in the absence of Dscam. Some types of OFF bipolar cells, type 3b and type 4 bipolar cells, had defects in dendrite arborization in the Dscam mutant retina, whereas other cell types appeared similar to wild type. The cone synapses that these cells project their dendrites to were intact, as visualized by electron microscopy, and had a distribution and density that was not significantly different from that of wild type. The spacing of type 3b bipolar cell dendrites was further analyzed by Voronoi domain analysis, density recovery profiling (DRP) analysis, and nearest neighbor analysis. Spacing was found to be significantly different when wild‐type and mutant type 3b bipolar cell dendrites were compared. Defects in arborization of these bipolar cells could not be attributed to the disorganization of inner plexiform layer cells that occurs in the Dscam mutant retina or an increase in cell number, as they arborized when Dscam was targeted in retinal ganglion cells only or in the bax null retina. Localization of DSCAM was assayed and the protein was localized near to cone synapses in mouse, macaque, and ground squirrel retinas. DSCAM protein was detected in several types of bipolar cells, including type 3b and type 4 bipolar cells. J. Comp. Neurol. 522:2609–2633, 2014. © 2014 Wiley Periodicals, Inc.